Development of artificial inoculation technique and cross infectivity test of Sclerotinia species on different hosts - PANDEY, K K; SAXENA, P; BHASKER, R B; BAHUKHANDI, D; TYAGI, P K (The Indian Journal of Agricultural Sciences, 2026)
Out of five inoculation techniques, the colonized petal method was best for quick and reproducible infections which can be successfully used for screening large number of germplasms at nursery stage, host pathogen interaction study, virulence test and race characterization. There was no significant difference in colony characters, sclerotial initiation period, arrangement and size of sclerotia in culture of different Sclerotinia species after inoculation on berseem and subsequent re-isolation. Initially sclerotial size was small and abundant in numbers but subsequently size increased and number decreased in berseem isolate. There was no significant difference in sclerotial weight of all the seven isolates when it was isolated from the cross inoculated hosts. It indicates that large sclerotia formation character of S. sclerotiorum from other hosts, changed in smaller sclerotia when inoculated on berseem. Indiscriminate colonization by Sclerotinia species on these hosts without any selective host specificity and no variation in cultural condition indicates that all may be same species of Sclerotinia. Confirmation of cross infectivity test on different hosts confirms that S. trifoliorum and S. sclerotiorum may be the same species to be known as S. sclerotiorum like Sclerotium rolfsii and Rhizoctonia solani.